2013
DOI: 10.1186/1471-2164-14-722
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale cold stress response regulatory networks in ten Arabidopsis thalianaecotypes

Abstract: BackgroundLow temperature leads to major crop losses every year. Although several studies have been conducted focusing on diversity of cold tolerance level in multiple phenotypically divergent Arabidopsis thaliana (A. thaliana) ecotypes, genome-scale molecular understanding is still lacking.ResultsIn this study, we report genome-scale transcript response diversity of 10 A. thaliana ecotypes originating from different geographical locations to non-freezing cold stress (10°C). To analyze the transcriptional resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 95 publications
3
41
1
3
Order By: Relevance
“…In nature, multiple factors usually contribute to a phenotype. Thus, in an accession study, a very high correlation between the level of one factor and the phenotype is rare (34,35). Consistently, in our results as well, there was only a weak negative correlation between A. brassicicola growth and AtABCG34 expression levels (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…In nature, multiple factors usually contribute to a phenotype. Thus, in an accession study, a very high correlation between the level of one factor and the phenotype is rare (34,35). Consistently, in our results as well, there was only a weak negative correlation between A. brassicicola growth and AtABCG34 expression levels (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Wang et al (2013) subjected Sha, Ler-1, and Col-0 accessions to salt treatment and identified a set of differentially expressed genes. Cold treatment also induced differential gene expression among accessions, and variations in expression levels were ascribed to polymorphic regions in gene promoters (Barah et al, 2013). Mild progressive WD also induced similar effects (Des Marais et al, 2012).…”
Section: Morphophysiological and Molecular Responses To Wd Vary Amongmentioning
confidence: 93%
“…In A. thaliana accession Col-0, increased SA was also responsible for plant stunting after shifting from 23°C to near chilling conditions (5°C) 22 . Exposure of other A. thaliana accessions to 10°C revealed genotype-specific expression patterns for ∼75% cold-regulated transcripts 23 , highlighting the extent of natural variation in temperature-modulated gene expression.…”
Section: Introductionmentioning
confidence: 94%